2018
DOI: 10.1111/pbi.12996
|View full text |Cite
|
Sign up to set email alerts
|

DELAYED HEADING DATE1 interacts with OsHAP5C/D, delays flowering time and enhances yield in rice

Abstract: Heading date is an important agronomic trait affecting crop yield. The GRAS protein family is a plant-specific super family extensively involved in plant growth and signal transduction. However, GRAS proteins are rarely reported have a role in regulating rice heading date. Here, we report a GRAS protein DHD1 (Delayed Heading Date1) delays heading and enhances yield in rice. Biochemical assays showed DHD1 physically interacts with OsHAP5C/D both in vitro and in vivo. DHD1 and OsHAP5C/D located in the nucleus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…There may be at least three reasons to explain this phenomenon: (i) Epigenetic mechanism. Previous evidence supported that the NF-Y transcription factor as important modulators of epigenetic marks controlling flowering [50][51][52][53] In summary, to elucidate the role of NF-Y transcription factor in poplar flowering induction and molecular regulation mechanism will be important for people to understand the role and function of NF-Y transcription factor family in woody plants, and provide important theoretical basis for regulating flowering time and shortening breeding cycle.…”
Section: Regulation Of Flowering Pathway Genes In the Transgenicmentioning
confidence: 88%
“…There may be at least three reasons to explain this phenomenon: (i) Epigenetic mechanism. Previous evidence supported that the NF-Y transcription factor as important modulators of epigenetic marks controlling flowering [50][51][52][53] In summary, to elucidate the role of NF-Y transcription factor in poplar flowering induction and molecular regulation mechanism will be important for people to understand the role and function of NF-Y transcription factor family in woody plants, and provide important theoretical basis for regulating flowering time and shortening breeding cycle.…”
Section: Regulation Of Flowering Pathway Genes In the Transgenicmentioning
confidence: 88%
“…RNAi suppression of the LFY ortholog RICE FLORICAULA (RFL) strongly delays flowering (Rao et al, 2008). Wheat VRN1, a homolog of AP1, also plays a critical role in spikelet development and spike determinacy (Li et al, 2019). Expression pattern analysis showed that WFL, a LFY homolog in wheat was upregulated by VRN1 and might be associated with lateral branching of spikelets in the inflorescence meristem (Shitsukawa et al, 2006).…”
Section: Accepted Articlementioning
confidence: 99%
“…In addition, we concluded that other transcription factors identified here also play roles in the phase change, because the functions of their putative homologues in other plants have been studied. For example, plants with elevated levels of a Dof transcription factor, CYCLING DOF FACTOR 1, flower late (Imaizumi et al 2005); a member of the MYB family, ASYMMETRIC LEAVES 1, accelerates flowering by increasing the amount of gibberellin-4 and facilitating CONSTANS to induce the expression of FLOWERING LOCUS T (Song et al 2012); in barley and rice, miR171 regulation of some members of the GRAS (GAI-RGA-SCR) family mediate the phase change from vegetative to reproductive development (Curaba et al 2013;Fan et al 2015), and in rice, another member of the GRAS family, DHD1, also controls the flowering time (Zhang et al 2019). Based on the expression patterns, annotations and predicted interactions of transcription factors identified here (Table 2), and the flowering time gene network in Arabidopsis thaliana (Blümel et al 2015;Song et al 2013), we propose a regulatory network model for the phase change from vegetative to reproductive development in larch (Fig.…”
Section: Regulatory Network Of the Phase Changementioning
confidence: 99%
“…Genes functioning to delay reproductive growth or maintain the state of vegetative growth have been identified from herbaceous plants, such as Arabidopsis, barley, and rice, including microRNA miR156 Wu et al 2009), miR171 (Curaba et al 2013;Fan et al 2015), DHD1 (DELAYED HEADING DATE1) (Zhang et al 2019), EMF1 (Embryonic Flower 1) and EMF2 (Sung et al 2003), TEM (TEMPRANILLO) (Sgamma et al 2014), and TFL1 (Terminal Flower 1) (Mohamed et al 2010;Kotoda and Wada 2005). In gymnosperm trees, genes functioning to change the timing of reproductive growth have also been identified; among them, DAL1, a MADS-box transcription factor from Picea abies, is expressed increasingly from age 5 years, and its over-expression in Arabidopsis results in early flowering (Carlsbecker et al 2004); in contrast, the overexpression of LaAP2L1 (a heterosis-associated AP2/EREBP transcription factor from Larix) results in late flowering in Arabidopsis (Li et al 2013b) and over-expression of the PEBP genes identified in conifers also represses flowering in Arabidopsis (Karlgren et al 2011;Klintenäs et al 2012).…”
Section: Introductionmentioning
confidence: 99%